Wildfowl on hydro-electric reservoirs in the Scottish Highlands - Mills, Derek; MacIver, Duncan (Wildfowl, 1964)
The value of hydro-electric reservoirs as wildfowl habitats is discussed, on the basis of a large number of counts made from April, 1962 to March, 1964 at Meig reservoir, Ross-shire. This was formed by the construction of a concrete dam across the River Meig by the North of Scotland Hydro-electric Board in 1956. The numbers of wildfowl were small, though above the average to be found on many neighbouring natural lochs and other reservoirs. Possible ways of making reservoirs more attractive to ducks include fencing stretches of shore to stop grazing, planting with semi-aquatic herbage, and the use of artificial islands.